Inclusive Digital Financial Services for Persons with Disabilities: Impact on Economic Empowerment and Financial Inclusion - Santoso, Bagus (Indonesian Journal of Disability Studies, 2023)
Financial inclusion has emerged as a policy concern in many countries, leading to various initiatives to promote financial inclusion for marginalised populations, including persons with disabilities (PwD). This research examines the usage of financial services by PwD in developed and developing countries through a systematic literature review (SLR) and relevant descriptive statistics. The findings shed light on significant barriers hindering PwD to financial services, such as information asymmetry, complex banking procedures, insufficient sensitivity towards disabilities that result in less accommodating financial services, and limited innovation in banking services. The findings suggest that improving financial literacy and adopting inclusive digital financial services are keys to improving financial inclusion for PwD.